Current control by electrode coatings formed by polymerization of dopamine at prussian blue-modified electrodes. Issue 6 (15th February 2016) - Gao, Bowen; Su, Lei; Yang, Hankun; Shu, Tong; Zhang, Xueji
Abstract : Electrode coating with polydopamine (PDA) is fast becoming a popular surface modification technique. Abstract : Electrode coating with polydopamine (PDA) is fast becoming a popular surface modification technique. In this study we report the investigation of the use of PDA as electrode coatings with Prussian blue (PB) as an electrode material model. The PB layer was galvanostatically deposited at an Au electrode, followed by PDA coating with the assistance of ammonium persulfate as an oxidant. The thickness of PDA coatings was measured to be ∼60 nm. Electrochemical characterization of the PDA-coated PB electrode revealed that the PDA coatings could stabilize the PB at neutral pH and allow the permeation of hydrogen peroxide (H2 O2 ). Moreover, the PDA coatings were found to effectively exclude the common interfering compounds such as cysteine, ascorbic acid and uric acid, and exhibit selective electrocatalysis towards the electroreduction of H2 O2 . Accordingly, the PDA-coated PB electrode was applied for determination of H2 O2 released from live cells.